2008
DOI: 10.1111/j.1523-5378.2008.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2C19 Genetic Polymorphisms on the Efficacy of Proton Pump Inhibitor‐Based Triple Therapy for Helicobacter pylori Eradication: A Meta‐Analysis

Abstract: The efficacy of omeprazole- and lansoprazole-based first-line triple therapies at the standard doses is dependent on CYP2C19 genotype status, which appears not to affect the efficacy of the regimens including rabeprazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 43 publications
4
71
0
4
Order By: Relevance
“…A sub-analysis of CYP2C19 influence on H. pylori eradication by individual PPI found significantly lower rate of eradication for NM compared to IM or PM for omeprazole and lansoprazole; this effect was not significant when esomerazole or rabeprazole were analyzed. Results of this meta-analysis were in line with another meta-analysis by Zhao et al [72], also documenting that patients with NM have lower odds of H. pylori eradication compared to IM and PM. The nonsignificant results for CYP2C19 effect on therapeutic outcomes of rabeprazole and esomeprazole in this meta-analysis and few other studies [71,73] can be explained by the lower contribution of CYP2C19 in esomeprazole and rabeprazole metabolism compared to other PPIs.…”
Section: Cyp2c19 and Ppi Pharmacogeneticssupporting
confidence: 89%
“…A sub-analysis of CYP2C19 influence on H. pylori eradication by individual PPI found significantly lower rate of eradication for NM compared to IM or PM for omeprazole and lansoprazole; this effect was not significant when esomerazole or rabeprazole were analyzed. Results of this meta-analysis were in line with another meta-analysis by Zhao et al [72], also documenting that patients with NM have lower odds of H. pylori eradication compared to IM and PM. The nonsignificant results for CYP2C19 effect on therapeutic outcomes of rabeprazole and esomeprazole in this meta-analysis and few other studies [71,73] can be explained by the lower contribution of CYP2C19 in esomeprazole and rabeprazole metabolism compared to other PPIs.…”
Section: Cyp2c19 and Ppi Pharmacogeneticssupporting
confidence: 89%
“…In additional subanalysis of individual PPIs revealed that omeprazole was influenced by the CYP2C19 genotype [143] . In another meta-analysis, successful eradication rates differed considerably between PM and HetEM (OR = 1.73, P = 0.002) and between PM and HomEM (OR = 2.79, P < 0.0001) and even between HetEM and HomEM (OR = 2.00, P < 0.0001) [144] . This study showed that…”
Section: Is Tailored Therapy On the Horizon For H Pylori Treatment?mentioning
confidence: 96%
“…South Korea Choi et al [189] a regimen including rabeprazole was not affected by CYP2C19 genotype status [144] . According to a metaanalysis of a RCT in 2013, regardless of the PPI being taken, the eradication rates of PM were higher than HetEM and HomEM [145] .…”
Section: Publication Treatment Duration Patients Therapy Regimen Eradmentioning
confidence: 98%
“…The metaanalysis and reviews revealed that metabolism of different drugs like proton pump inhibitors has little association with CYP2C19 genotype [35][36] . Study also suggests that the dose of few drugs can be increased in populations with high frequencies of HomEMs or HetEMs 37 .…”
Section: Discussionmentioning
confidence: 94%